2011
DOI: 10.1007/s11738-011-0739-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient plant regeneration of Malaysian indica rice MR 219 and 232 via somatic embryogenesis system

Abstract: Improvement on rice plant regeneration system from an embryogenic callus using two Malaysian indica rice MR 219 and MR 232 was developed in this study. Different stages of rice explants (zygotic embryos) were tested for callus induction and regeneration using various carbon sources and amino acids. The present study shows that dough stage of zygotic embryos was the best stage of explants for the embryogenic callus induction and regeneration of both rice cultivars. The embryogenic callus nature with the compact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…1 and 2). Zuraida et al 44 reported that CI frequency depends on genotype, and most indica rice cultivars had poor callusing potentiality. In this case we examined the CI potentiality using 4 hormonal combinations (H 1 , H 2 , H 3 and H 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). Zuraida et al 44 reported that CI frequency depends on genotype, and most indica rice cultivars had poor callusing potentiality. In this case we examined the CI potentiality using 4 hormonal combinations (H 1 , H 2 , H 3 and H 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Followed by rinsed three times in deionized water (Zuraida et al, 2012). Sterilized seeds were cultured on MS media (Murashige and Skoog, 1962) supplemented with 3% sucrose, 0.3% gelrite and 2 mg L -1 2, 4-D (pH 5.8) to induce the formation of MR219 callus.…”
Section: Seed Sterilization and Callus Inductionmentioning
confidence: 99%
“…Seeds of various recalcitrant plant species like Indica rice may possess restrictions in promoting callus in vitro culture (Thokozani et al 2013). Efforts have been made to find appropriate rice explants to induce embryogenic calli under suitable in vitro conditions (Zuraida et al 2011).…”
Section: Introductionmentioning
confidence: 99%